Determining The Quantities Knives of The Chopper of Cotton Stems - Auezov Ongarbay Pyrleshovich; Baltanyazov Adilbay Sarsenbayevich (Zien Journals, 2022)
The article gives the importance of grinding cotton stalks before chilly plowing, which helps to increase soil plowing and urazhinost. For this purpose, a cotton stem shredder was developed and the results of a theoretical study of the working process of a cotton shredder are given.
Keywords: Cotton; stems; chopper; knives